Taxonomic notes on feather grasses (Poaceae: Stipa) from eastern Kazakhstan with typification of seven names and one new combination - Nobis, Marcin; Gudkova, Polina D. (Phytotaxa, 2016)
The genus Stipa comprises approximately 50 taxa in Kazakhstan, of which 18 were described by Yuri A. Kotukhov from eastern Kazakhstan between 1987 and 1998. The majority of the original material of these taxa is preserved in the LE herbarium (Saint-Petersburg, Russia). Some original material of Kotukhov’s species, not mentioned in the protologues, is preserved in the KUZ (Kemerovo, Russia) and KRA (Krakow, Poland) herbaria. The present paper presents a complete list of feather grasses described by Kotukhov from Kazakhstan, with indications of types and the locations where they are preserved, lectotypification of seven names (S. akseirica, S. argillosa, S. karakabinica, S. kempirica, S. kyzylkiensis, S. azutavica, S. saikanica), one new combination (S. orientalis var. azutavica comb. nova), synonymisation of three species (S. akseirica is a synonym of S. sareptana, S. kyzylkiensis is a synonym of S. sczerbakovii, and S. saikanica is a synonym of S. lessingiana), an identification key and taxonomic notes regarding the discussed taxa.